2019
DOI: 10.1002/asna.201913663
|View full text |Cite
|
Sign up to set email alerts
|

The study of coherent optical pulsations of the millisecond pulsar PSR J1023+0038 on Russian 6‐m telescope

Abstract: We observed the millisecond redback pulsar PSR J1023+0038 in its accreting regime on two nights in November 2017 on Russian 6-m telescope with a high-temporal resolution panoramic photometer-polarimeter in a two-channel ("blue" and "red") setup. During 400 s (12% of nearly 3 hr of total observations), we detected coherent optical pulsations in both color bands with 1.69-ms period, corresponding to the rotational period of neutron star known from the radio data, with amplitudes of 2.1% ("red") and 1.3% ("blue")… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The unique observational property of J1023 is millisecond optical pulsations, first found by [2] and confirmed in subsequent studies (e.g. [3][4][5]). The pulse profile has two peaks with variable amplitudes, reaching about 1 percent in the maximum.…”
Section: Introductionsupporting
confidence: 53%
“…The unique observational property of J1023 is millisecond optical pulsations, first found by [2] and confirmed in subsequent studies (e.g. [3][4][5]). The pulse profile has two peaks with variable amplitudes, reaching about 1 percent in the maximum.…”
Section: Introductionsupporting
confidence: 53%
“…Soon after, we succeeded in detecting them with Aqueye+@Copernicus, for the first time with a 2-m class telescope (Zampieri et al, 2019a). Other detections both in the optical (Karpov et al, 2019) and UV bands (Jaodand et al, 2021) were also reported since then.…”
Section: Psr J1023+0038: the First Ms Optical And Uv Pulsarmentioning
confidence: 84%
“…Quite surprisingly, also the optical emission observed from PSR J1023+0038 turned out to be pulsed with an rms amplitude of 1% [142,56,143,144]. This made PSR J1023+0038 the first optical MSP to date.…”
Section: The Sub-luminous Disc Statementioning
confidence: 92%